2019
DOI: 10.1108/apjml-10-2018-0396
|View full text |Cite
|
Sign up to set email alerts
|

Understanding female consumers’ intention to shop online

Abstract: Purpose The purpose of this paper is to develop a model to examine the female consumer’s intention to shop online. The rising number of female online shoppers has compelled the analysts and online vendors to believe that understanding the attitude and behaviour of the female consumers is very crucial for their growth. Design/methodology/approach A conceptual model is proposed that expands the theory of reasoned action (TRA) with three additional constructs, namely, trust, convenience and customer service. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(48 citation statements)
references
References 97 publications
(121 reference statements)
3
39
0
6
Order By: Relevance
“…As to ensure a valid and reliable evaluation from the customers, it would be more appropriate for online shopping study to consider only the existing customers who have adequate experience with buying products through online shopping website (Awad and Ragowsky, 2008;Al-Debei et al 2015;Chin and Goh, 2017;Raman, 2019). Thus, consistent with many of the previous studies that set six months to qualify for the customers to evaluate their attitudes and behaviours (Han et al 2009;Han and Kim, 2010;Kilger and Romer, 2007), the respondents of online shopping study should also fixed to customers who have been using the online shopping platforms to purchase any products for at least six months.…”
Section: Target Populationmentioning
confidence: 99%
“…As to ensure a valid and reliable evaluation from the customers, it would be more appropriate for online shopping study to consider only the existing customers who have adequate experience with buying products through online shopping website (Awad and Ragowsky, 2008;Al-Debei et al 2015;Chin and Goh, 2017;Raman, 2019). Thus, consistent with many of the previous studies that set six months to qualify for the customers to evaluate their attitudes and behaviours (Han et al 2009;Han and Kim, 2010;Kilger and Romer, 2007), the respondents of online shopping study should also fixed to customers who have been using the online shopping platforms to purchase any products for at least six months.…”
Section: Target Populationmentioning
confidence: 99%
“…TR has been the focus of a great deal of attention and extensively study in numerous contexts such as banking (Chang & Hung, 2018), retailing (Wobker et al, 2015), online shopping (Raman, 2019) and mobile shopping (Jimenez et al, 2016). Given the massive expansion of mobile devices, findings in the marketing literature have shown that trust plays an important role as a precedent for good perception for mobile shopping as well as maintaining long-term buyer and seller relationships.…”
Section: Trust (Tr)mentioning
confidence: 99%
“…This research defines trust as the consumer belief, confident or expectation of mobile shopping that fulfil their needs and not taking unexpected actions produces negative results. A great number of prior studies have demonstrated that trust is the most vital aspect that determines a consumer's behaviour (Chang & Hung, 2018;Raman, 2019;Jimenez et al, 2016). Chang and Hung (2018) stated that trust is an important predictor of behavioral outcomes in the context of mobile banking.…”
Section: Trust (Tr)mentioning
confidence: 99%
“…Several studies investigating online purchase intentions made use of the Theory of Reasoned Action or Theory of Planned Behavior in order to explain future online purchase intentions (Raman, 2019;Chin and Goh, 2017;Butt et al, 2017). The theory of reasoned action (TRA) explains the relationship between attitude and behaviour (Ajzen, 1991) and suggests that human beings are rational individuals with the ability to process decision-making information.…”
Section: Literature Review Overview Of Online Purchase Intentionmentioning
confidence: 99%